Haemodynamic, hormonal, and electrolyte effects of enalapril in heart failure. Issue 2 (August 1983) - Fitzpatrick, D; Nicholls, M G; Ikram, H; Espiner, E A
Abstract : Enalapril, the new converting enzyme inhibitor, was administered to eight patients with heart failure (NYHA Functional Class II to IV) during standardised and intensive haemodynamic, hormone, and electrolyte monitoring. The first dose (5 mg) of enalapril induced a fall in plasma angiotensin II and noradrenaline levels, and prolonged decrements in systemic vascular resistance, arterial pressure, heart rate, and right heart pressures. Maximum haemodynamic effects were evident four to eight hours after the first dose, with return to baseline by 24 hours. Plasma angiotensin II levels, however, were still suppressed at 24 hours. The magnitude of haemodynamic response was related closely to baseline (pre-enalapril) activity of the renin-angiotensin system and the sympathetic system. Enalapril treatment over three days induced a positive cumulative balance of sodium and potassium, and a small increase in plasma potassium. Urine aldosterone excretion decreased in a stepwise fashion. Continued enalapril administration for four to eight weeks resulted in improved clinical status (NYHA Functional Class) and exercise tolerance in patients who initially were most severely incapacitated, but little change was observed in healthier subjects. We conclude that in heart failure, enalapril is a long acting converting enzyme inhibitor with clear cut beneficial haemodynamic effects in the short term. Long term controlled studies of enalapril in heart failure are warranted.